Methods and Results of the Brain and Visceral Organs Protection During the Correction of the Ascending Aorta and Aortic Arch Aneurysm or Isolated Aortic Arch Aneurism - V. I. Kravchenko; I. M. Kravchenko; I. I. Zhekov; V. D. Lybavka; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2021)
The ascending aorta and aortic arch aneurysm surgical correction is the most difficult problem of cardiovascular surgery due to the necessity of management of the main disease and adequate protection of the brain and visceral organs.The aim. To present the methods and results of protection of the central nervous system and visceral organs during the correction of the ascending aorta and aortic arch aneurysm or isolated aortic arch aneurism.Materials and methods. During 1994–2018, we operated 419 patients with the ascending aorta and aortic arch aneurysm (or isolated aortic arch aneurism).Diagnosis of aneurysms was based on clinical data, transthoracic and transesophageal echocardiography, computed tomography, X-ray examination, aortography.All operations were performed under general anesthesia, through the median sternotomy using cardiopulmonary bypass. Valve-sparing technique with aortic valve resuspension/aortic valve plasty and semi-arch/arch replacement was used in 288/9 (68.7%) patients. Bentall operation with semi-arch/arch replacement was used in 86/9 (20.5%) patients. Other operations accounted for 45 (10.7%) patients.Results. The history of the development of aortic aneurysms treatment options is briefly overviewed in the paper. Diagnostic methods are mentioned, but the main method today is computed tomography. Initial status of the patients was severe. All operations were performed through median sternotomy using cardiopulmonary bypass. The following techniques were used for surgical treatment of aneurysms: 1) valve-sparing technique with aortic valve resuspension/ plasty and semi-arc/arch replacement was used in 288/9 (68.7%) patients. In this group there were 8 Yacoub operations, 6 David operations. In 7 patients, plication of one of the leaflets was performed in case of aortic valve prolapse. 3 patients underwent strengthening of the free edge of the leaflets and 4 patients underwent plasty by the patch in case of leaflet fenestrations; 2) Bentall operation with semi-arch/arch replacement was used in 86/9 (20.5%); 3) others: isolated arch in 15 (3.6%); Wheat operation + arch in 9 (1.0%); aortic arch plasty in 4 (1.0%); Elephant trunk (conventional Elephant trunk) + TEVAR was used in 17 (4.1%) patients. The brain protection was performed differently at each of the two stages in our surgical experience. The best result was achieved at the last stage. The number of postoperative complications decreased from 34.4% to 8.4% and hospital mortality from 17.2% to 5.3%, respectively. Also, a modern endovascular method – hybrid operations Elephant trunk + TEVAR – was used in 17 (4.1%) patients with good immediate result.Conclusions.1. At type A aortic dissection (DeBakey type I) the operation of choice is supracoronary ascending aortic replacement with a semi-arch (arch) replacement of the aorta.2. Accumulation of surgical experience, team training, improvement of methods of protection of the brain and visceral organs allowed to reduce the number of postoperative complications from 34.4% to 8.4% and hospital mortality from 17.2% to 5.3%.